Numerical Simulation of Dynamic Analysis of Glacier Under Seismic Loading Based on Combined Finite-Discrete Method. (May 2019) - Su, Y.; Liu, E.l.
Abstract: The dynamic analysis of the Laohugou No.12 Glacier of Qilian Mountain under given seismic loading effect is analyzed by using combined finite-discrete element method (FDEM). The necessary ice parameters for FDEM simulation are calibrated by using numerical experiments of biaxial compression corresponding to the physico-mechanical parameters. The results indicated that the stress-strain curves are strain softening, and the peak value of deviatoric stress is consistent with the laboratory experiments. Under the dynamic load effect, the glacier slip along the slope direction, and the whipping effect of the speed is obvious. The feasibility of using FDEM method to study discontinuous problems such as ice avalanche is discussed.